Antropofagia, intertextualidade e carnavalização na tradução do texto literário para o cinema em Vidas Secas, Macunaíma e Auto da Compadecida - Grossi, Elvair (2013)
The present study investigates and analyzes the movies: Vidas Secas (1963), by Nelson Pereira dos Santos; Macunaíma (1969), by Joaquim Pedro de Andrade, and Auto da Compadecida (2000), by Guel Arraes, all of them based on literary narratives. Our discussion will cover elements present in the process of formation and organization of Brazilian culture, such as cannibalism, intertextuality and carnivalization. To this end, we will use the concepts of writing, dialogism and carnivalization, based on Bakhtin s work and his circle; the concept of intertextuality, the relation between "I" and the "other", from Bakhtin and Kristeva s work; and the concept of cannibalism, as elaborated by Oswald de Andrade. Assuming that every film is a cultural text and based on these theorists, we try to identify each stage of constitution of this process, using films or meshes whose texts are constituents of literary narratives: a text, a discourse or a Brazilian novel that has been transformed into an image, a film discourse and, from this theoretic axis, to analyze the presence of intertextuality, carnivalization and cannibalism in the construction of filmic text; to verify how the transposition of the literary text to the filmic text occurred, as well as the importance of dialogism, carnivalization and cannibalism as elements that structure, organize and set the unit of meaning; comparison of the literary text with the filmic text regarding to the ideas (content) and the structure. In that order, presenting the cinema as a filmic text, as a tissue of the media structured by complex discursive lines, the study organizes a corpus from three Brazilian films, of which we discuss, in the line of Metz and Bellour, the editing structures of cinematograph enunciation, the framing and the linearity, that allows the organization and understanding of the narrative of filmic text and the conversion to the literary text. In the field of aesthetics, editing and visual metaphors, we seek the theories of Eisenstein and Bazin, because we understand that in the filmic texts (Brazilian cinema) and its interaction with literary novels, language strategies (verbal signs) and visual strategies (nonverbal signs) will allow to experience the formation of our culture, taking into account their sign systems